System Design Applications Android Based Mobile Library - Fathiah, Fathiah; Hardi, Richki (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2015)
The success and development of the current android capable of occupying the highest position gadgets and computer market, it is certainly due to the sophistication of technology systems and applications that are on it are currently a trend among mobile users because it can help all areas of work so that it becomes easier. The advantages of this android is located on an open source license so it is possible for anyone with an android programming ability to create or develop applications to run on Android-based gadgets. Library is one of the facilities which assist in the provision of resources in the educational process because the library provides lending facilities without any cost burdened. To expedite the process of search services and lending by the borrower to the library, we need a system that allows the members of the library to access library services, especially the process of borrowing books online using android based mobile application library. This study will integrate mobile application library with the Library Information System simulation database used in the Library of the Sekolah Tinggi Teknologi Bontang. This application is one of the technological development which is very helpful in facilitating mobile library services based course with the gadget android who has installed this application.Â Keywords: Android Gadget, Mobile Library, Opensource